A Walk Through the History and Exploring the Conservation Project of Lalbagh Kella, an Incomplete Mughal Fort of Dhaka, Bangladesh (American Journal of Interdisciplinary Research and Innovation, 2023)
Lalbagh Fort was possibly the most significant construction project performed by Dhaka’s Mughal kings. Despite the fact that the complex was named “Lalbagh Fort” because of the huge defensive fortifications and gates, the masterplan and layouts of the structures that now survive bore little or no resemblance to other Mughal settlements in Bangla or elsewhere in India.The complex’s development lasted just a decade before it became uninhabited for unknown reasons. The brief history of the fort had been buried since 1688, and it remains unfinished to this day. Many efforts have been made to bring this monument’s legacy back to life after decades of oblivion. The main challenge appears to be the incomplete nature of the construction, as well as the scarcity of archaeological materials, literary evidence, and epigraphic texts available to architectural historians. Filling up this gap with these seemingly inconspicuous materials has undoubtedly confounded the existing conversation about this monument.This confusion characterizes Lalbagh’s architecture today. It raises a slew of concerns about its initial master plan, function, and construction history, to which we have yet to offer definitive answers due to the telescopic distance. This research attempts to investigate and evaluate many competing hypotheses concerning its architecture and the continuing conservation process. The fundamental goal is to depict the architecture and examine the conservation process.